2000
DOI: 10.1128/aem.66.1.425-427.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phoma glomerataas a Mycoparasite of Powdery Mildew

Abstract: Ampelomyces and Phoma species are frequently confused with each other. Isolates previously attributed to the genus Ampelomyces were shown to be Phoma isolates through studies of their morphology and life cycle and ribosomal DNA internal transcribed spacer region 1 sequence analysis. Phoma glomerata can colonize and suppress development of powdery mildew on oak and may have utility as a mycoparasitic agent.Powdery mildews are widespread plant pathogens that are conspicuous by their white mycelia and powder-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 12 publications
3
53
0
1
Order By: Relevance
“…Until recently, A. quisqualis was often confused with several other species: A. quercinus, A. humuli, A. heracli and Phoma glomerata. Unlike A. quisqualis, these other powdery mildew mycoparasites do not produce intracellular pycnidia and they also grow more quickly, with in vitro radial growth rates of 3-4 mm d −1 (Kiss et al 2004;Sullivan and White 2000). In the past, scientists identified all of these fast-growing strains as A. quisqualis (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Until recently, A. quisqualis was often confused with several other species: A. quercinus, A. humuli, A. heracli and Phoma glomerata. Unlike A. quisqualis, these other powdery mildew mycoparasites do not produce intracellular pycnidia and they also grow more quickly, with in vitro radial growth rates of 3-4 mm d −1 (Kiss et al 2004;Sullivan and White 2000). In the past, scientists identified all of these fast-growing strains as A. quisqualis (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Genetic diversity and heterogeneity within various A. quisqualis isolates have been shown by several molecular studies on restriction fragment length polymorphism (RFLP) (Kiss 1997), single-stranded conformation polymorphism (SSCP) (Szentivá nyi et al 2005), and phylogenetic sequence analyses of ITS rDNA region (Kiss & Nakasone 1998;Sullivan & White 2000;Liang et al 2007). In addition, Kiss (1997), Nakasone (1998), andSzentivá nyi et al (2005) showed that genetically diverse Ampelomyces isolates were largely divided into two distinct clades, each of which was characterized by fast or slow growth in culture.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Kiss (1997), Nakasone (1998), andSzentivá nyi et al (2005) showed that genetically diverse Ampelomyces isolates were largely divided into two distinct clades, each of which was characterized by fast or slow growth in culture. It was suggested that fast-growing Ampelomyces isolates be reidentified as Phoma glomerata based on the results of molecular analysis and the difference of pycnidia formation (Sullivan & White 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Most Phoma species are cosmopolitan species and have been recognized as common plant pathogens. P. gromerata and P. macrostoma in the same clade with KY-1 in the ITS1-5.8S rRNA-ITS2 distant tree are noted because of the interesting characteristics in agriculture (Sullivan and White 2000;Zhou et al 2004). However, Mn oxidation is not among their characteristics.…”
Section: Resultsmentioning
confidence: 95%